The Cs-137 Shrimp Tragedy: A Revolution in Quality and Supply Chain Protection Paradigms for Consolidating the Economic Competitiveness of Indonesian Shrimp. - Aldi Adi Pratama (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2025)
The detection of Cesium-137 (Cs-137), a highly toxic, artificial radionuclide, in frozen Indonesian shrimp exports to the United States (US) market precipitated a severe crisis, significantly jeopardizing the national fisheries sector's reputation. The contamination source was traced to the downstream environment, specifically a processing facility in the Cikande Industrial Complex, Banten, presumably linked to the unintentional or illegal importation of contaminated industrial raw materials. This descriptive-analytical qualitative study utilized Documentary Research and Content Analysis on secondary data from governmental bodies (KKP, BAPETEN, BPS) and public media. The methodological contribution is the Data Source Triangulation protocol applied to official reports, statistical data, and public documentation, ensuring the consistency and rigor of the findings. The core finding confirms that the crisis exposed a profound corporate Environmental, Social, and Governance (ESG) Failure marked by deficiencies in accountability and risk management within a supporting industrial sector (metal recycling) that directly impacted the core supply chain (fisheries exports). Crucially, the government's swift, science-based, and transparent crisis response, spearheaded by BAPETEN and KKP, proved instrumental in restoring international confidence. The Novel Insight is the US FDA's subsequent designation of the KKP Quality Agency as the Certifying Entity (CE) for Cs-137-free certification. This strategic action transformed Indonesia from a reactive compliance violator into a globally recognized Standard Setting Nation. This outcome enriches Crisis Communication literature with a model focused on Science Based Regulatory Capability Enhancement. The study underscores the imperative to institutionalize this success into a proactive, integrated quality infrastructure and stricter corporate due diligence to guarantee long-term export sustainability.